Extracellular Vesicles Secreted by Astroglial Cells Transport Apolipoprotein D to Neurons and Mediate Neuronal Survival Upon Oxidative Stress - Pascua-Maestro, Raquel; González, Esperanza; Lillo, Concepción; Ganfornina, Maria D.; Falcón-Pérez, Juan Manuel; Sanchez, Diego (Frontiers in Cellular Neuroscience, 2019)
Extracellular vesicle (EV)-mediated glia-to-neuron communication has been recognized in a growing number of physiological and pathological situations. They transport complex sets of molecules that can be beneficial or detrimental for the receiving cell. As in other areas of biology, their analysis is revolutionizing the field of neuroscience, since fundamental signaling processes are being re-evaluated, and applications for neurodegenerative disease therapies have emerged. Using human astrocytic and differentiated neuronal cell lines, we demonstrate that a classical neuroprotective protein, Apolipoprotein D (ApoD), expressed by glial cells and known to promote functional integrity and survival of neurons, is exclusively transported by EVs from astrocytes to neurons, where it gets internalized. Indeed, we demonstrate that conditioned media derived from ApoD-knock-out (KO) astrocytes exert only a partial autocrine protection from oxidative stress (OS) challenges, and that EVs are required for ApoD-positive astrocytic cell line derived medium to exert full neuroprotection. When subfractionation of EVs is performed, ApoD is revealed as a very specific marker of the exosome-containing fractions. These discoveries help us reframe our understanding of the neuroprotective role of this lipid binding protein and open up new research avenues to explore the use of systemically administered ApoD-loaded exosomes that can cross the blood-brain barrier to treat neurodegenerative diseases.